PENGARUH JOB INSECURITY TERHADAP KESEJAHTERAAN DAN KINERJA KARYAWAN KONTRAK PADA KANTOR PUSAT ADMINISTRASI UNIVERSITAS SYIAH KUALA BANDA ACEH - Sri Murni, Yurnalis (Departemen Manajemen, 2018)
: The contract work system is one of the phenomena of internal change in the order and system of work that is almost done by every organization. Like Syiah Kuala University which also uses contract labor. In its development, there was a problem in the employment of employees with a contract work system, namely the emergence of conditions of job insecurity felt by employees. Job insecurity allows it to affect the welfare and performance of contract employees. The purpose of this study was to determine the effect of job insecurity on welfare and the performance of contract employees at the Syiah Kuala University Administrative Office Banda Aceh. This research is a quantitative research using SPSS data analysis method using SPSS version 2.0 software. The population in this study were all contract employees at the Syiah Kuala University Administration Head Office Banda Aceh. Sampling with simple random sampling technique uses the Slovin formula. The number of samples in this study amounted to 176 samples. The results of testing the hypothesis, indicate that the variable: job insecurity has a negative and significant effect on welfare, Job insecuriry has a negative and significant effect on performance. Keywords: job insecurity, welfare, performance, contract employees